Urban food environments through the lens of adolescents in Addis Ababa, Ethiopia - Trübswasser, Ursula; Baye, Kaleab; Holdsworth, Michelle; Loeffen, Megan; Feskens, Edith J. M.; Talsma, Elise F. (International Food Policy Research Institute, 2020)
In a recent study, adolescents living in Addis Ababa reported that food safety and affordability were their top concerns when making food purchases. Nutrition was a secondary concern: the students reported that even if the food sold were healthy, they would not purchase it if the vendor or outlet did not appear clean. Packaged foods were often perceived as healthy choices among the adolescents because they have labels featuring information such as expiry dates and the packaging is perceived to protect these foods from germs. Involving adolescents and their families in future research, programming, and interventions can help convey messages about the importance of nutrition. Providing clean, affordable, and healthy food options in and around schools can help ensure adolescents are able to choose and consume foods that meet all these important criteria. Ensuring that the food-based dietary guidelines under devel-opment in Ethiopia are used to provide nutrition education could help adolescents apply the guidelines in their daily life.